Recent foraminifera from the Croatian Adriatic seacoast - Cosovic, Vlasta; Juracic, Mladen; Moro, Alan; Kucenjak, Morana Hernitz; Rukavina, Sanja; Pugliese, Nevio; Stuper, Natasa; Vlahov, Ines (Anuário do Instituto de Geociências, 2006)
Abstract